Understanding Visitor Engagement at Private Art Spaces: A Mixed-Methods Study of A Non-Profit Gallery in Indonesia - Zafira Meizzati Indraputri; Novika Candra Astuti (Community Engagement and Emergence Journal (CEEJ), 2025)
Private art spaces occupy an unusual position in the cultural landscape. They carry public-facing missions—education, cultural dialogue, community building—yet operate without the institutional funding that sustains government museums. This study examines factors shaping visitor engagement at Gallery XYZ, a non-profit contemporary art institution located in a major creative city in Indonesia. Despite years of programming exhibitions, workshops, and cultural events, the gallery faces inconsistent attendance and a narrow visitor demographic. The research employed a convergent mixed-methods design, integrating quantitative survey data (n=162) with qualitative semi-structured interviews (n=11). Survey respondents were categorized into three segments: current visitors (n=88), aware non-visitors who recognized the gallery but had never attended (n=34), and those entirely unaware of its existence (n=40). Thematic analysis following Braun and Clarke's framework identified six interrelated themes: motivational drivers, engagement barriers, visitor experience quality, brand perception, communication effectiveness, and value perception. Quantitative findings revealed that 81.8% of visitors were irregular—either lapsed or one-time attendees. Access and distance emerged as the dominant barrier (67.0% of visitors, 31.1% of non-visitors). The companion dependency pattern proved equally notable: 61.4% visited with friends, while 25-31% across segments cited lacking a companion as a barrier. Qualitative findings revealed a perception gap—the gallery commanded prestige among art insiders yet remained largely invisible to the general public. Non-visitors described galleries as spaces "made for other people," suggesting psychological barriers that practical interventions alone may not address. The study contributes to cultural marketing literature by illustrating how private art spaces in developing economies may inadvertently cultivate exclusive reputations despite inclusive aspirations.